PEST VISUALIZATION AND DISEASE IN CORN CROP USING MICROSOFT VISUAL BASIC 6.0 - Ferry Sugianto; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2003)
Use of Computer Applications as one tool to provide information on livestock farming. The use of computer applications that are specifically analyze about pests and diseases that attack corn plants by displaying information about the symptoms, pest / disease causes and how to control pests and diseases will be providing a solution for users who are interested to cultivate maize.